Developing a HospiSE scale for hospital service excellence. Issue 3 (25th February 2014) - Ho Voon, Boo; Abdullah, Firdaus; Lee, Nagarajah; Kueh, Karen
Abstract : Purpose: – This empirical survey research aims to identify the dimensions of service excellence culture for hospitals. Ultimately, a measurement tool was developed for hospital service excellence (i.e. HospiSE scale). Design/methodology/approach: – The survey research involved qualitative and quantitative approaches in the scale development process. The structured questionnaire was carefully designed after literature review and focus groups discussions. The respondents were employees from the public and private hospitals in Malaysia. A total of 1, 558 usable questionnaires were used for the quantitative analysis. The HospiSE scale was empirically tested for reliability and validity through exploratory and confirmatory factor analyses. Findings: – This measurement-oriented research had identified three dimensions of service excellence culture for hospitals, namely: employee orientation, patient orientation and competitor orientation. The multi-dimensional measure consists of 21 items. Research limitations/implications: – Longitudinal research is required to provide evidence of the causal effects of HospiSE on employee satisfaction and loyalty. The HospiSE scale also requires further verification and refinement. Practical implications: – The parsimonious scale can serve as a strategic and practical measure to evaluate and manage service excellence culture at hospitals. Reliable and valid information can be obtained for fast and cost-effective diagnosis of the service culture for continuous improvement. Social implications: – The new scale is expected to be an important diagnostic to understand and measure service excellence culture at hospitals. The patients and society at large will benefit from the improved hospital service management. Originality/value: – The multi-item measurement tool is new and it can provide insights into service management, resource allocation and human resource management for excellent hospital service. The measurement development process is contextualized for the hospital services.